Does Avalanche Shovel Shape Affect Excavation Time: A Pilot Study - Kurt Schindelwig; Alexander Hoffmann; Martin Mössner; Werner Nachbauer (MDPI AG, 2017)
In Europe and North America, approximately 150 fatalities occur as a result of avalanches every year. However, it is unclear whether certain shovel shapes are more effective than others in snow removal during avalanche victim recovery. The objective was to determine the performance parameters with a developed standardized test using different shovel shapes and to determine sex-specific differences. Hence, several parameters were determined for clearing the snow from a snow filled box (15 men, 14 women). A flat (F) and a deep (D) shovel blade with the shaft connected straight (S) or in clearing mode (C) were used for the investigation of the shovel shapes FS, DC and the subsequent use of DC&DS. Mean snow mass shifted per unit time increased significantly from 1.50 kg/s with FS to 1.71 kg/s (14%) with DS and further to 1.79 kg/s (4%) with DC&DS for all participants. Snow mass shifted per unit time was 44% higher (p < 0.05) for men than for women. In excavation operations, the sex-specific physical performance should be taken into account. The results were limited to barely binding snow, because only with this snow did the tests show a high reliability.